Digitalization and its impacts on bank profitability and credit during Covid-19 - Kerbeg, Marco Antonio (2025)
This study investigates the relationship between digitalization, bank profitability, and credit in Brazil, with a particular focus on the impact of the COVID-19 pandemic. Us ing detailed bank-level data, we construct a specific measure of digitalization, defined as the ratio of intangible assets to non-current assets. Our findings reveal that more digital ized banks exhibit higher profitability, measured by ROA, and that this effect intensified during the pandemic, as social distancing accelerated the adoption of digital banking ser vices. Additionally, we analyze the impact of digitalization on credit during the pandemic. We observe that more digitalized national private and state-owned banks expanded their credit supply compared to less digitalized institutions, while this trend was not observed among foreign private banks. In state-owned banks, digitalization fostered the provision of higher-quality credit and reduced the volume of lower-quality credit. We also find that more profitable public banks concentrated their lending in lower-risk operations. Among national private banks, leverage was positively associated with certain credit categories, whereas in foreign banks this relationship was predominantly negative. Our results high light the critical role of digitalization in strengthening the resilience of the financial sys tem, enhancing profitability, and shaping credit dynamics—especially during periods of crisis.